Jupito ’s (The Adjustable Bag) / Nur Izzaty Mohd Salim - Nur Izzaty, Mohd Salim (2020)
Business concepts that we used in business platform is direct selling ,which means is social media , online channel and website. Bacause , nowadays, social media is a reference to the way people interact where they create or share information and ideas in communities , virtual networks and places for people communicate or selling . The online channels that we used is a instagram, and facebook. This is because, this two applications are most popular nowadays . So, from that we take the advantage of this opportunity by selling our stuff through instagram and facebook. For channel website website store is JUPITO'S.com. Our product are handmade , because our product are limited . Otherwise , is target market. The target market in this business are mostly to student and employee . First, student. We are made specially designed for students and especially student studio base. What is a student studio base, is a student who uses large amounts of paper and bring many item. So, with this adjustable bag, it is perfect for this kind of student. However, students who are not studio based can also apply. Other than that, our product for appropriate student in age 18 years. So, it’s a bit appropriate. Second, for employee. This is because, for some workers like architecture and engineering. It's is why , these people carry so much stuff like paper and so on. So, with this adjustable bag, it really is a good fit. So, it is suitable for both. Next, the age of use of this bag is from 25 years and above. In addition, is competitive advantage in our product which means is adjustable bag. This is because the bag can carry A2 size item. This is because the bag can be changed to tote-bags. So from that , it's designed for large size items, like paper works . The manufacture of this bag can also be guaranteed to be safe .This has made easier for customers to carry the item with just one bag. The adjustable bag are also waterproof and durable. The profitability that we get is 70% that we get from 2019-2020. This is because our quality product that we used in our adjustable bag. That make costumer are love our product. From that, the profitability got a lot of response from people.